Restauración, automatización y puesta a punto de máquina extrusora para moldeo de plástico por soplado para la empresa Cantiplast S.A.S. (2024)
The following project managed to automate the blow molding machine that has been out of service for 3 years. This project was carried out in the company Cantiplast S.A.S, located in Bogota. This company is dedicated to the manufacture of plastic products using recycled material. The project included the delivery of the operational machine. The company supported financing for the purchase of parts and necessary supplies and the installation of the automation system.